The Concept of Digital Morals and Media Literacy Strategies in Muhammadiyah Educational Institutions to Face Disruption - Munfarih, Nahwah Al Falu; Inayati, Nurul Latifatul (Universitas Muhammadiyah Surakarta, 2025)
The current massive digital disruption phenomenon has triggered a worrying moral crisis in the virtual public sphere. This condition is characterized by the high intensity of the spread of misinformation (hoaxes), cyber provocation, hate speech, and the erosion of civilized communication ethics. Muhammadiyah, as a da'wah organization oriented towards renewal and educational enlightenment, responds to these challenges responsively by strengthening media literacy based on Islamic moral principles. This study aims to explore in depth the construction of the concept of digital morality in Islamic education and the systematic mechanisms for implementing media literacy in Muhammadiyah educational environments through a review of organizational policy documents. This study applies a qualitative approach with a library research method (library reserch). The researcher acts as a key instrument in collecting data through documentation studies. The research data sources are classified into primary data, which include fiqh documents, information on the tarjih and tajdid councils of PP Muhammadiyah, and the Al-Islam and Muhammadiyah curriculum (AIK), and secondary data from relevant scientific literature. Data analysis is carried out systematically using content analysis techniques (content analysis) which includes the stages of reduction, data presentation, and drawing conclusions to synthesize the construction of digital morality in Muhammadiyah Education policies and practices. Research findings indicate that the digital moral framework from Muhammadiyah's perspective is fundamentally oriented toward the values of tabayyun (verification), the polite manifestation of amar ma'ruf nahi munkar (enjoining good and forbidding evil), and theological awareness of the afterlife's accountability in every digital interaction. The implementation of this literacy has been proven to go beyond mere mastery of technical skills (technical skills), emphasizing the internalization of Information Fiqh ethics as a behavioral guideline for the entire academic community. The synergy between official organizational policies, an adaptive AIK curriculum, and a robust educational infrastructure is Muhammadiyah's fundamental strategy in mitigating the impact of moral disruption in the digital era. The success of this model sets an important precedent for Islamic education in producing a generation that is not only technologically savvy but also possesses spiritual depth and moral integrity in the virtual world.